STANDARDS OF CREATIVE TEACHER PERFORMANCE - Nurika Khalila Daulay (VISION, 2016)
Teacher's creativity should be applied in critical thinking skills and a lot of ideas and a lot of ideas, so that they can see the same thing but with a different way of thinking, especially the meaning of quality education services in the context of learning.Keywords: Standard, performance, teacher.